History Strikes Back : How States, Nations, and Conflicts Are Shaping the 21st Century - Vedrine, Hubert (Book collections on Project MUSE., 2008)
"Offers an overview of world politics since the fall of the Berlin Wall. Takes issue with the belief that states are unnecessary and globalization and free markets will make a better world. Promotes a 'smart Realpolitik' to guide West relations with emerging powers, manage globalization, and deal with environmental challenges"--Provided by publisher.